Analysis and design of multi-stage LQR UPFC - Pandey R.K. (My University, 2025)
This paper presents stability analysis and design of multi-stage LQR unified power flow controller (UPFC) for multimachine power system based on generalized modelling approach. An improved LQR control has been proposed as Multi-Stage LQR which considers the predominant eigenvalues of system for selection of weights of Q matrix that gives very fast tracking for a given disturbance. The approach is modular and general enough so as to include any sub system along with detailed representation. The performance of multi-stage LQR UPFC has been evaluated for a sample two area system which can readily be extended to multi-area with some augmentation. ©2010 IEEE.